Differential down-regulation and induction responses of testicular steroidogenic cytochromes P-450(cscc) and P-450(C17α) to human choriogonadotropin. Issue 5 (May 1986) - Kühn-Velten, Nikolaus; Bos, Dagmar; Staib, Wolfgang
Abstract : Evidence is presented that the regulation of the cytochrome P-450(C17α) of the steroid-17α-monooxygenase and of the cytochrome P-450(cscc) of the cholesterolmonooxygenase by human choriogonadotropin (hCG) in vivo is mediated by differential mechanisms in the adult rat testis. An initial down-regulation of the cytochrome P-450(C17α) but not of the P-450(cscc) can be demonstrated. Furthermore, induction of the cytochrome P-450(cscc) requires exposure to higher hCG doses (3270 of the maximal induction rate of 43.7 pmol/(testis x d) are achieved with 4 IU hCG/single dose) than induction of the P-450(C17α) (59% of the maximal induction rate of 48.4 pmol/(testis x d) with 4 IU hCG/single dose), Finally, induction ofcytochrome P-450(cscc) starts faster after initiation of hCG treatment than induction of P-450(C 17α).